Frequency of molecular detection of equine coronavirus in faeces and nasal secretions in 277 horses with acute onset of fever. (23rd March 2019) - Pusterla, Nicola; James, Kaitlyn; Mapes, Samantha; Bain, Farifield
Abstract : Context: Due to the inconsistent development of enteric signs associated with ECoV infection in adult horses, many practitioners collect nasal secretions rather than feces for the molecular diagnostic work‐up of such horses. Main conclusion: ECoV infection should be considered in horses presenting with acute onset of fever, especially when nasal discharge is absent as one of the cardinal clinical sign. Approach: A total of 277 adult horses with acute onset of fever were enrolled in this study. Feces were tested for ECoV and nasal secretions for common respiratory pathogens (equine herpesvirus (EHV)‐1, EHV‐4, equine influenza virus (EIV), equine rhinitis viruses (ERVs) and Streptococcus equi ss. equi ) and ECoV by qPCR. Each submission was accompanied by a questionnaire requesting information pertaining to signalment, use, recent transportation, number of affected horses on the premise and presence of clinical signs at the time of sample collection. Results: The total number of horses testing qPCR‐positive for ECoV in feces was 20 (7.2%), 4 of which also tested qPCR‐positive for ECoV in nasal secretions. In the same population 9.0% of horses tested qPCR‐positive for EHV‐4, 6.1% for EIV, 4.3% for Streptococcus equi ss. equi, 3.2% for ERVs and 0.7% for EHV‐1. Draft horses, pleasure use, multiple horses affected on a premise and lack of nasal discharge were significantly associated with ECoV qPCR‐positive horses. Interpretation: The present study results showed that 7.2% of horses with acute onset of fever tested qPCR‐positive for ECoV in feces, highlighting the importance of testing such horses for ECoV in feces. The various prevalence factors associated with ECoV qPCR‐positive status likely relate to the high infectious nature of ECoV and breed‐specific differences in management and husbandry practices. Significance of findings: ECoV infection should be suspected and tested for in horses presenting with acute onset of fever, lethargy and anorexia with no respiratory signs. A two‐step approach should be consider in which respiratory secretions and feces should be collected from such horses and submitted to a diagnostic laboratory. If the respiratory secretions test negative by qPCR for a panel of respiratory pathogens, feces already submitted to the laboratory should be tested for ECoV.